Analisis Empiris Dampak Kebijakan Fiskal Terhadap Pertumbuhan Ekonomi Di Kalimantan Tengah (2014–2023) - Bismart Arituan; Abdul Halim; Pratiwi Subianto (Ecoplan, 2025)
This study examines the impact of fiscal policy on economic growth in Central Kalimantan during the period 2014-2023. As a province rich in natural resources, Central Kalimantan faces challenges in optimizing fiscal policy to promote sustainable economic growth and reduce development disparities between regions. This research aims to evaluate the effectiveness of fiscal policy implementation, analyze the impact of budget allocation on leading economic sectors, and examine its influence on equitable economic development across regions. The research methodology employs a quantitative approach with panel data analysis for the period 2014-2023 covering 13 regencies and 1 city in Central Kalimantan. Based on the Hausman test results, the fixed effects model was selected as the best model with GRDP as the dependent variable and independent variables including capital expenditure, infrastructure spending, PAD, and transfer funds. The research results show a significant relationship between fiscal policy and economic growth with a capital expenditure elasticity coefficient of 0.284 and a multiplier effect of 1.42. The construction sector shows the highest elasticity (0.412) to capital expenditure, followed by manufacturing industry (0.385) and agriculture (0.276). Regional inequality analysis shows a decrease in the Williamson Index from 0.412 (2019) to 0.364 (2023). In conclusion, fiscal policy has a positive impact on regional economic growth but still requires optimization in terms of budget allocation, strengthening regional fiscal capacity, development equalization, and developing comprehensive monitoring systems.